Jaramillo, Samuel (2009), Hacia una teoría de la renta del suelo urbano, Bogotá, Universidad de Los Andes - Schteingart, Martha (El Colegio de México A.C., 2012)
Jaramillo, Samuel. (2009).  Hacia una teoría de la renta del suelo urbano, Bogotá, Universidad de Los Andes.